In vitro blood brain barrier exposure to mycotoxins and carotenoids pumpkin extract alters mitochondrial gene expression and oxidative stress. (July 2021) - Alonso-Garrido, M.; Frangiamone, M.; Font, G.; Cimbalo, A.; Manyes, L.
Abstract: Food and feed are daily exposed to mycotoxin contamination which effects may be counteracted by antioxidants like carotenoids. Some mycotoxins as well as carotenoids penetrate the blood brain barrier (BBB) inducing alterations related to redox balance in the mitochondria. Therefore, the in vitro BBB model ECV304 was subcultured for 7 days and exposed to beauvericine, enniatins, ochratoxin A, zearalenone (100 nM each), individually and combined, and pumpkin extract (500 nM). Reactive oxygen species were measured by fluorescence using the dichlorofluorescein diacetate probe at 0 h, 2 h and 4 h. Intracellular ROS generation reported was condition dependent. RNA extraction was performed and gene expression was analyzed by qPCR after 2 h exposure. The selected genes were related to the Electron Transport Chain (ETC) and mitochondrial activity. Gene expression reported upregulation for exposures including mycotoxins plus pumpkin extract versus individual mycotoxins. Beauvericin and Beauvericin-Enniatins exposure significantly downregulated Complex I and pumpkin addition reverted the effect upregulating Complex I. Complex IV was the most downregulated structure of the ETC. Thioredoxin Interacting Protein was the most upregulated gene. These data confirm that mitochondrial processes in the BBB could be compromised by mycotoxin exposure and damage could be modulated by dietary antioxidants like carotenoids. Highlights: BEA and BEA-ENs downregulated Complex I, while pumpkin addition reverted the effect. CIV (MT-CO1 and MT-CO3) was the most downregulated complex of the ETC. TXNIP was the most upregulated gene for all conditions but BEA and BEA-ENs. MT-RNR2 was strongly downregulated for all exposures but BEA.